PERAN RADIO KOMUNITAS DWIJENDRA 107.7 FM DALAM PENGEMBANGAN SIARAN KEARIFAN LOKAL BALI - Gede Bagus, Anak Agung (Dwijendra University, 2019)
Radio community  is one of the broadcasting institutions which legalized the existence of Broadcasting Law No.32 of 2002. According to Broadcasting Law No. 32 of 2002 article 13, providers of broadcast services (television and radio). The problem is how the role of the Dwijendra Radio Community 107.7 FM Broadcast Local Wisdom of Bali, the purpose of this study is to find out how the role of community radio as a medium for the development of local wisdom broadcasts. This research is descriptive qualitative, the subject of this research is the person in charge of broadcasting local wisdom broadcasts, data collection techniques are done by interview techniques, observation techniques, and documentation techniques. The results showed that the role of community radio as an educational medium is manifested in the form of broadcast programs that elevate local culture, manifested through broadcast programs that are arranged and presented in a creatively packaged program. The local wisdom broadcast of Radio Community Dwijendra 107.7 fm is an event Gegitaan. Where the event was broadcast during the daytime 12.05-14.00 wita.